IMPACT OF FINANCING RISK ON PROFITABILITY OF ISLAMIC BANKS - Afif , Zineb; Sehaqui , Camélia; Haissoune , Mohamed (International Journal of Islamic Banking and Finance Research, 2025)
Banks, as financial intermediaries, face a variety of risks that significantly affect their performance and stability. Islamic banks, like conventional banks, are particularly vulnerable to financing risk, which directly affects their profitability and, if not properly managed, can lead to severe financial distress or even bankruptcy. The purpose of this study is to investigate the relationship between financing risk and the profitability of Islamic banks operating in the MENA region. This research utilizes a panel dataset comprising 14 Islamic banks over ten years from 2013 to 2022. Profitability is measured through the return on assets (ROA), while financing risk is assessed using the nonperforming financing ratio, the financing-to-asset ratio, and the capital adequacy ratio. The study employs panel regression analysis to evaluate secondary data extracted from banks' financial reports. The results indicate that both the financing-to-asset ratio and the capital adequacy ratio have a positive impact on the return on assets, suggesting that a well-managed financing structure and robust capital adequacy contribute to enhancing bank profitability. Conversely, the findings reveal that the nonperforming financing ratio negatively impacts the return on assets, highlighting the detrimental effects of poor financing quality on overall bank performance. The significant findings of this study suggest that Islamic banks should place a greater emphasis on mitigating financing risk through maintaining a strong capital base, diversifying their portfolios, and implementing effective credit risk management practices. This approach would not only enhance profitability but also safeguard the banks against potential losses and financial crises.JEL Classification Codes: G21, F65, C23.